Effect of the Puyehue-Cordon Caulle volcanic complex eruption on crustacean zooplankton of Andean lakes - Balseiro, Esteban Gabriel (2014)
We studied the effect of volcanic ash on the crustacean zooplankton (mainly cladocerans) in the Andean North-Patagonian lakes that were affected by the eruption of the Puyehue-Cordón Caulle complex. The study was carried out at three different scales: sub cellular, population and ecosystemic. Cladocerans are filter feeding organisms that cannot distinguish between food (algae less than 30 µm) and suspended ash, therefore when feeding they ingest this material. The ash affected negatively the individuals at a biochemical level, increasing the oxidative stress reacting enzymes like Glutation-S-transferase and the biomarker Acetyl cholinesterase. At the population level, we recorded a decrease in survival and fecundity, in particular, when ash concentration exceeded 8 mg/L, we observed that individuals did not reach adulthood. At the ecosystem level, we recorded a significant decrease of the intermediate trophic level (primary consumers) although producers were positively enhanced by the eruption. The absence of these primary consumers may affect upper trophic levels like fishes. Later, in the year following the eruption, we observed the resurgence of zooplankton populations suggesting a fast recovery from the initial conditions.